Ozone's Antimicrobial Potential: A Review Article - , Matéus Simplício Araújo; , Yann Nobre Viana; , Joelson Pessoa Dantas; , Antônio Evandro de Sousa Silva; , Guilherme Salles Ottoboni; , Poliana Lima Bastos; , Francisco César Barroso Barbosa (Archives of Current Research International, 2025)
Objective: The importance of investigating new products with antimicrobial activity (AA) is based on the constant increase in the frequency of reports of antimicrobial resistance that hinder the treatment of human infections. This integrative literature review aimed to investigate the potential antimicrobial activity (AA) of O3 and elucidate its importance in the context of the need for bioprospecting of new antimicrobial agents. Methodology: For this purpose, a search for articles published between July 2014 and July 2024 was carried out in the PubMed, Scielo and Cocharne databases. Four keywords were established and verified on the DeCs - Health Sciences Descriptors website, namely “ozone”, “antimicrobial activity”, “antibacterial” and “antifungal”. The search and critical reading of studies related to the AA of ozone in 3 databases led to the inclusion of 11 articles. Results: ozone is a molecule that indeed has antimicrobial potential and its use occurs in different physical forms, such as the application of ozone in gas, in aqueous form, in oily vehicles or even in nanoparticles. Discussion: It was observed that there is a need for more clinical studies and animal models to evaluate the applicability of O3 in infectious conditions in vivo, such as dentoalveolar abscesses, skin infections and respiratory and digestive tract infections, since the vast majority of articles found belonged to laboratory-based in vitro assays. Conclusion: Ozone has a wide AA, therefore representing an important product for bioprospecting in the context of antimicrobial agents. The need for more clinical studies is highlighted.